The Islamic Terms in Moufdi Zakaria’s Poems : A Lexicographic and Semantic Study (Journal of the College of Education for Women, 2019)
This study seeks to examine the language context of the prominent Revolution’s poet, Moufdi Zakaria, in his anthology “ The Algerian Odyssey " )إلياذة الجزائر( in which he makes use of the Coranic terms explicitly and implicitly. Besides, it seeks to explore the content of his terms from a lexicographic and semantic point of view in their Islamic and human dimensions